Mental Toughness And Its Relationship To Some Variables Among Middle School Students - محمود طه عبدالحميد (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
Mental toughness plays an important role in helping students confront, overcome, and recover from problems, challenges, and crises. It also helps students control emotions, develop self-confidence, believe in and adhere to decisions, and develop their self-esteem when facing these challenges. Students with weak mental toughness may experience diminished achievement, distracted minds, and diminished determination and competence. This is especially true since middle school students need this mental toughness to achieve academic excellence and psychological stability. It acts as a protective shield for them in the face of difficulties and in seeking appropriate opportunities to develop and enhance their capabilities in all aspects of their personality. (Madid: 2023). Recent years have witnessed a growing interest in positive concepts in psychology, given that. The research aimed to identify the level of mental toughness among university students and the statistically significant differences in the level of mental toughness according to the variable of gender (males - females), specialization (scientific - literary), and type of study (morning - evening). The current research community included middle school students for the academic year (2023-2024), whose number was (12463), and the research sample included (400) male and female students. The research required preparing a research tool to measure the level of mental toughness. By reviewing a number of literature and previous studies, the researcher prepared a research tool that is compatible with the nature of the sample and the research problem. To analyze the data and extract results, the researcher used a number of appropriate statistical tools and methods. The results showed that the sample members enjoyed a good level of mental resilience and that there were no statistically significant differences in the level of mental resilience and the type of study, and that there was a statistically significant difference in the level of mental resilience at a significance level of (0.05). In light of the results, the researcher presented a number of recommendations and proposal.